A Duty Cycle Controlled ZVS Buck Converter With Voltage Doubler Type Auxiliary Circuit - Basharat, Sana; Awan, Saeed Ehsan; Akhtar, Rizwan; Hussain, Alamdar; Iqbal, Shahid; Shah, Sayyar Ali; Yuan, Aihua (Frontiers in Energy Research, 2021)
DC–DC converters have wide applications in industries, motor drive circuits, electric vehicles, and power supplies. In traditional converters hard switching occurs due to switching losses. This imposes constraints on the converter’s efficiency which results in heat dissipation and reduction in the converter’s life. The proposed converter aims to encounter the hard switching problem with the provision of soft switching features. The presented topology is efficient with respect to the features of cost, compact size and durable lifetime of converter topology with the provision of low switching stresses. This research work proposes a novel stepdown converter with zero voltage switching characteristics. With the use of half bridge inverter switches and series resonant components in the auxiliary circuit, the target of zero voltage switching and reduction in switching stresses has been achieved. The proposed 500 W converter is designed to operate at frequency of 100 KHz with 300 V source input voltage. Output voltage of the converter is 150 V.